Effects of conus peptides on the behavior of eudriles eugeniae (affrican nightcrawler) and danio rerio (zebrafish) - Esteban, Ramiel S.; Gener, Dayanara Mika E.; Zabaldica, Mariem Shem O. (2014)
Vemivorous species of Conus are commonly underutilized due to the assumption that their active venom components are much lesser stronger than those found in piscivore species. Lyophilized venom crude extract from vermivorous Conus embraeus was administered via intraperitoneal injection of 0.2357 mg/L to Eudrilus eugeniae and Danio rerio to assess its bioactive potency. Since E. eugeniae are known for exhibiting negative phototaxis, they were subjected to the dark preference test. The rate of movement towards darkness of treated E.eugeniae was found to be significantly different from the untreated at p=0305. On the other hand, toxicological responses in D.rerio upon administration of the crude extract were assessed by observations in the change in region preference test, duration of freezing bouts, and occurrence of erratic movements. These bioassays were done during the day and at night to consider their diurnal behavior. Results showed that freezing bouts and erratic movements were more pronounced in zebra fishes treated at night while geotaxis increased regardless of the time of treatment. Data gathered from this study therefore indicate that the crude extract has bioactive potential which can be of pharmacological use.
Thesis (Bachelor of Science) -- University of the Philippines Baguio, 2014.
Includes bibliographical references (leaves 34-38)